(3GdfMhs - (3GdMSf Hf eMeO GdCUHgGfj, CHh Ydj GdeYQha HdZOI, Ch dZPI Ch dcPI, hdYdg HGdcGa GdeYbhOI,J (B311 (3g` s
(3ChdgG (B:s
(3GdcdGe cdg KdGKI CTjGA GSe haYd hMQa, LGA deYfi djS HGSe hdG aYd, aGdGSe fMh bhdc, QLd, aQS s
(3BNQgG (B:s
(3hEdi cdGH hCfeGQ hVHGH hEPG cGfJ GSekG ddbHGFd hGdCMjGA cdGHj hVHGHj hCfeGQj GfbVi cJGH GdfMh hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HNW cHjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B238s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B327 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs